Positive effects of liana cutting on seedlings are reduced during El Niño‐induced drought - O'Brien, M; Philipson, C; Reynolds, G; Dzulkifli, D; Snaddon, J; Ong, R; Hector, A (Wiley, 2019)
1.Liana cutting is a management practice currently applied to encourage seedling regeneration and tree growth in some logged tropical forests. However, there is limited empirical evidence of its effects on forest demographic rates in Southeast Asia. 2.We used 22 four‐hectare plots in the Sabah Biodiversity Experiment (a reduced impact logging site) enrichment line planted with 16 dipterocarp species to assess the effects of complete liana cutting on tree growth and survival. We compared plots where lianas were only cut along planting lines (standard enrichment line planting) with those with one (2014) or two rounds (2011 and 2014) of complete liana cutting. 3.We found increased seedling growth following the first complete liana cut in 2011 relative to the enrichment line planting, consistent with previous studies. The response after three years to the cutting in 2014 depended on whether lianas had been previously cut or not: in twice‐cut plots, seedling growth was not significantly different from the standard enrichment planting controls, whereas growth in plots with only one complete cut in 2014 was significantly slower. Seedling survival decreased through time for both once‐ and twice‐cut liana treatments but remained stable in controls. 4.Sapling growth after the 2014 liana cutting showed a similar pattern to seedling growth, while tree growth following the 2014 liana cutting was significantly lower than controls regardless of whether lianas were cut twice (2011 and 2014) or once (2014). 5.Differences in response between the two rounds of liana cutting were likely due to changes in precipitation ‐ 2011 was followed by consistent rainfall while 2014 was followed by two severe droughts within two years. 6.Synthesis and applications. Our results generally support the widely‐reported positive effects of liana cutting on tree growth and survival. However, reduced growth and survival after the 2015/16 El Niño suggests that drought may temporarily undermine the benefits of liana cutting in logged tropical forests. Managers of similar areas in SE Asia should consider halting liana cutting during El Niño events. In other tropical areas, seedling survival should be monitored to assess to what extent results from SE Asia are transferable.